Are theory of intelligent design and neo-darwinism complementary? - Wójcik, Bogusław (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2007)
Today the theory of evolution is under attack from the point of view of Intelligent Design (ID), which remains not only intellectual position but a political movement too. In some interpretations ID is a continuation of the Creationism; in others ID is coherent with the scientific background. According to W. A. Dembski ID is best characterized by three things: ’a scientific research program that investigates the effects of intelligent causes; an intellectual movement that challenges Darwinism and its naturalistic legacy; and a way of understanding divine action’. Taking account of this situation it is extremely important to reinforce the dialogue between true science and theology. God of the New Testament remains the source of the innovation and from this perspective neither chance in nature excludes God, nor destiny in nature requires God. These and other reasons lead one to accept the position of Cardinal J. H. Newman: ’I believe in design because I believe in God, not in a God because I see design’.Today the theory of evolution is under attack from the point of view of Intelligent Design (ID), which remains not only intellectual position but a political movement too. In some interpretations ID is a continuation of the Creationism; in others ID is coherent with the scientific background. According to W. A. Dembski ID is best characterized by three things: ’a scientific research program that investigates the effects of intelligent causes; an intellectual movement that challenges Darwinism and its naturalistic legacy; and a way of understanding divine action’. Taking account of this situation it is extremely important to reinforce the dialogue between true science and theology. God of the New Testament remains the source of the innovation and from this perspective neither chance in nature excludes God, nor destiny in nature requires God. These and other reasons lead one to accept the position of Cardinal J. H. Newman: ’I believe in design because I believe in God, not in a God because I see design’.